Intervention Landscape of the CGIAR Agroecology Initiative in El Rhahla Region – Siliana District/Tunisian Agroecological Living Landscape - Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2022)
Intervention Landscape of the CGIAR Agroecology Initiative in El Rhahla Region – Siliana District/Tunisian Agroecological Living Landscape.